General Mobilization in Algeria and the Restrictions Imposed on its Declaration and Termination - Attou , Rachid (Journal of Legal Studies and Researches, 2026)
General mobilization in Algeria is an exceptional measure called for by necessity, regulated by the Constitution and the law—particularly Article 99 and Law No. 25-05—to confront threats endangering national security (military, natural, health-related, economic, etc.). Its exercise is subject to restrictions intended to protect individual rights and freedoms and to prevent the abuse of exceptional measures.